2015
DOI: 10.1093/ntr/ntv027
|View full text |Cite
|
Sign up to set email alerts
|

“Smoker’s Paradox” in Patients Treated for Severe Injuries: Lower Risk of Mortality After Trauma Observed in Current Smokers

Abstract: Patients who smoke appear to have a much lower risk of in-hospital mortality than nonsmokers. Further investigation into biological mechanisms responsible for this effect should be carried out in order to potentially develop therapeutic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
4
11
0
Order By: Relevance
“…Furthermore, it has been described that smoking might significantly reduce the number of complications and mortality in severely injured patients, which is known as the 'smoker's paradox'. 19 Similar outcomes have been described among patients with cardiovascular disease. 20 However, the potential protective mechanisms behind this phenomenon and its clinical implications are not well established.…”
Section: Open Accesssupporting
confidence: 58%
“…Furthermore, it has been described that smoking might significantly reduce the number of complications and mortality in severely injured patients, which is known as the 'smoker's paradox'. 19 Similar outcomes have been described among patients with cardiovascular disease. 20 However, the potential protective mechanisms behind this phenomenon and its clinical implications are not well established.…”
Section: Open Accesssupporting
confidence: 58%
“…The protective effect we found on short-term outcomes post AMI could also be similar to the “smoker’s paradox,” referring to the observed short-term mortality benefit in tobacco users post AMI [ 16 , 17 ]. Several studies over the past 20 years have described a mortality benefit conferred in tobacco users in the 30-day period post AMI, especially with use of thrombolytic therapy for treatment [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 70%
“…Trauma patients who smoke do not consistently have worse outcomes compared to non-smokers [41]. In fact, several studies have demonstrated a lower mortality in adult smokers following a traumatic injury [38,42,43]. This phenomenon is termed the "smoker's paradox," and was originally described in adult patients who sustained acute myocardial infarction [44][45][46].…”
Section: Discussionmentioning
confidence: 99%